The Role Of CT In Early Diagnosis Of Lung Cancer (The Review of Diabetic Studies, 2024)
Lung cancer remains a leading cause of cancer mortality globally, with early detection being essential for improving survival outcomes. Low-dose computed tomography (LDCT) has emerged as a superior screening modality compared to chest X-ray (CXR), demonstrating consistent reductions in lung cancer-specific mortality through large randomized controlled trials. LDCT’s enhanced sensitivity enables detection of smaller, early-stage nodules amenable to curative treatment, although its relatively low positive predictive value results in notable false-positive rates and concerns about overdiagnosis. Technical advances in LDCT protocols, including dose optimization and iterative reconstruction, balance image quality with radiation exposure, supporting repeated annual screenings. Integration of artificial intelligence and biomarker assays offers promising avenues to improve diagnostic specificity and reduce unnecessary interventions, yet these adjuncts require further validation across diverse populations. Meta-analyses confirm LDCT’s mortality benefit alongside increased early-stage detection and surgical resection rates, while highlighting challenges related to false positives, overdiagnosis, and equitable access. Ethical considerations emphasize informed consent, harm minimization, and resource allocation, particularly in varied healthcare settings. Future strategies should focus on refining eligibility criteria, optimizing follow-up algorithms, and incorporating emerging technologies to maximize net benefit and minimize harms in lung cancer screening programs.